2021
DOI: 10.1111/imb.12726
|View full text |Cite
|
Sign up to set email alerts
|

Active genic machinery for epigenetic RNA modifications in bees

Abstract: Epitranscriptomics is an emerging field of investigation dedicated to the study of post‐transcriptional RNA modifications. RNA methylations regulate RNA metabolism and processing, including changes in response to environmental cues. Although RNA modifications are conserved from bacteria to eukaryotes, there is little evidence of an epitranscriptomic pathway in insects. Here we identified genes related to RNA m6A (N6‐methyladenine) and m5C (5‐methylcytosine) methylation machinery in seven bee genomes (Apis mell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
16
0
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 107 publications
5
16
0
8
Order By: Relevance
“… Bataglia et al (2021) reported that global levels of m 6 A and m 5 C methylation quantified in the total RNA from brain and fat body samples increases in age progression. In this study we observed an increase in the expression of RNA methyltransferases in brain which is in accordance with the overall increase in global m 6 A and m 5 C methylation levels ( Bataglia et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… Bataglia et al (2021) reported that global levels of m 6 A and m 5 C methylation quantified in the total RNA from brain and fat body samples increases in age progression. In this study we observed an increase in the expression of RNA methyltransferases in brain which is in accordance with the overall increase in global m 6 A and m 5 C methylation levels ( Bataglia et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“… Bataglia et al (2021) reported that global levels of m 6 A and m 5 C methylation quantified in the total RNA from brain and fat body samples increases in age progression. In this study we observed an increase in the expression of RNA methyltransferases in brain which is in accordance with the overall increase in global m 6 A and m 5 C methylation levels ( Bataglia et al, 2021 ). However, in the fat body, although the higher expression of RNA methyltransferases is found in younger bees, the global m 6 A and m 5 C methylation levels are lower in young bees when compared with older bees.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, epigeneic modifications such as DNA methylation, microRNA, and alternative chromatin states have been shown to be involved in the regulation of honeybee queen-worker dimorphism ( Foret et al., 2012 ; Ashby et al., 2016 ; Guo et al., 2016 ; Wojciechowski et al., 2018 ). The latest evidence showed that m6A methylation on RNA also participates in the genomic regulation leading to queen-worker dimorphism ( Bataglia et al., 2021 ; Wang et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Early works leading to the discovery of the mRNA Cap structure have detected a low level of internal 5-methylcitosine (5-mC) in the mammalian and insect cells 19 , 20 . Later studies have also detected the presence of methylated nucleotides in viral RNAs 21 , 22 .…”
Section: Introductionmentioning
confidence: 99%